Creating Markets for Biotechnology - Walsh, Vivien (The International Journal of Sociology of Agriculture and Food, 2021)
Much recent literature on biotechnology has focused on supply side issues such as technological opportunities and applications, or organisational changes in the innovating firms. This paper examines the demand side of biotechnology, focusing on GM foods in particular, and analysing the creation of a selection environment in which the innovation might diffuse. In neo-Schumpeterian economics, the concept of 'selection environment' is used to mean the features of the environment of the firm that determine whether innovations succeed or fail. Creating a market is not only an economic but also a social-shaping activity, and the selection environment is a wider and more complex and subtle concept than a market. This paper has drawn on several disciplinary perspectives to analyse the phenomenon, in particular on sociology, anthropology and evolutionary economics. The many elements of the selection environment for agrobiotechnology included the market of consumers; potential consumers (some of whom resisted the new technology); the regulatory system; retailers; policy makers; environmentalists; consumer organisations; the intellectual property régime; intermediaries which promoted the new products, which informed consumers, and which raised areas of concern; the politicisation of the whole process; and the market creation activities of the innovating firms (especially Monsanto). Monsanto's promotional activities, which would normally fall within the realm of traditional market creating behaviour, in the context of other elements of the selection environment had a counter effect. It generated a learning process in which the companies concerned discovered the merits of trying to open up a dialogue with other elements of the selection environment.